Subtype Identification of Surgically Curable Primary Aldosteronism During Treatment With Mineralocorticoid Receptor Blockade - Pintus, Giovanni; Seccia, Teresa Maria; Amar, Laurence; Azizi, Michel; Riester, Anna; Reincke, Martin; Widimský, Jiří; Naruse, Mitsuhide; Kocjan, Tomaz; Negro, Aurelio; Kline, Gregory; Tanabe, Akiyo; et al. (Hypertension (Dallas, Tex., 2024)
BACKGROUND: Current guidelines and consensus documents recommend withdrawal of mineralocorticoid receptor antagonists (MRAs) before primary aldosteronism (PA) subtyping by adrenal vein sampling (AVS), but this practice can cause severe hypokalemia and uncontrolled high blood pressure. Our aim was to investigate if unilateral PA can be identified by AVS during MRA treatment. METHODS: We compared the rate of unilateral PA identification between patients with and without MRA treatment in large data sets of patients submitted to AVS while off renin-angiotensin system blockers and β-blockers. In sensitivity analyses, the between-group differences of lateralization index values after propensity score matching and the rate of unilateral PA identification in subgroups with undetectable (≤2 mUI/L), suppressed (<8.2 mUI/L), and unsuppressed (≥8.2 mUI/L) direct renin concentration levels were also evaluated. RESULTS: Plasma aldosterone concentration, direct renin concentration, and blood pressure values were similar in non-MRA-treated (n=779) and MRA-treated (n=61) patients with PA, but the latter required more antihypertensive agents (P=0.001) and showed a higher rate of adrenal nodules (82% versus 67%; P=0.022) and adrenalectomy (72% versus 54%; P=0.01). However, they exhibited no significant differences in commonly used AVS indices and the area under the receiving operating characteristic curve of lateralization index, both under unstimulated conditions and postcosyntropin. Several sensitivity analyses confirmed these results in propensity score matching adjusted models and in patients with undetectable, or suppressed or unsuppressed renin levels. CONCLUSIONS: At doses that controlled blood pressure and potassium levels, MRAs did not preclude the identification of unilateral PA at AVS. REGISTRATION: URL: https://www.clinicaltrials.gov; Unique identifier: NCT01234220.
Keywords: dospělí; Mineralocorticoid Receptor Antagonists; tendenční skóre; Female; aldosterone; Adult; výsledek terapie; ženské pohlaví; Renin; adrenalektomie; lidé; hyperaldosteronism; aldosteron; mineralocorticoid receptor antagonists; nadledviny; studie případů a kontrol; Treatment Outcome; krevní tlak; Adrenalectomy; retrospektivní studie; Hyperaldosteronism; Male; Aldosterone; Case-Control Studies; Adrenal Glands; lidé středního věku; hypertension; mužské pohlaví; hyperaldosteronismus; Blood Pressure; blood pressure; Retrospective Studies; renin; Middle Aged; Propensity Score; antagonisté mineralokortikoidních receptorů; Humans